Regeneration and demolition vis-á-vis disintegration of urban space: The case of el Cabanyal-Canyamelar in Valencia - Kazimierczak, Jarosław. Autor; Wrona, Karolina. Autor (IGiPZ PAN, 2019)
Disintegration of urban space is the opposite of its organisation; regeneration should be discussed in this context as it restores or introduces morphological attributes that meet the needs of local communities. The paper identifies the impact of regeneration upon urban space (re)integration and the role of planned demolition as a regeneration tool on the example of el Cabanyal-Canyamelar district in Valencia, Spain. Studies have demonstrated that demolition can be considered a rational component of regeneration and that not only morphological attributes of the transformed area are important for urban space regeneration but also intentions and ways of using demolition as a regeneration tool.
24 cm
Keywords: desintegration of urban space; dysfunctionality; regeneration; demolition; el Cabanyal-Canyamelar; Valencia